Detection of Autoimmune Antibody Among Some Chronic Lymphocytic Leukemia Sudanese Patients - Khartoum, Sudan (2008) - Mohammed Ahmed, Ozaz Yagoub; Siddig, Mohamed Abd Elmonien (Gezira Journal of Health Sciences, 2013)
Introduction: Few data are available concerning the prevalence of autoimmune disease in chronic lymphocytic leukemia patients at diagnosis as well as at clinical outcome. This study was carried out in the radioisotope center in Khartoum - department of blood bank from the period 2 August to 20 September 2008. Aim: The aim of this study is to detect the presence of auto-immune antibody among chronic lymphocytic leukemia patients. Method: Two ml of venous blood were collected from 50 CLL patients of both sexes and different ages. All specimens were tested for autoimmune antibody by using direct Coomb's by the immune diffusion gel technique. A structured pre tested questionnaire was used to collect the qualitative data  Results Analysis showed that 38% of the patients have autoimmune antibody in their serum. Also it confirmed that there is significant difference between the presence of autoimmune antibody, jobs (0.004), the duration of the disease (0.019) and there is no significant difference between the presence of autoimmune antibody and age (0.051) as well as the sex of the patients (0.960). Recommendations : CLL patient must be investigated for autoanibodies, which can help in improving management and enhance controlling the prognosis of the patient.    الخلاصة مقدمة : البيانات المتوفره قليلة بخصوص انتشار الاضداد منيعة الذات المتعلقة بمرض ابيضاض الدم الليمفاوي المزمن سواء أكانت عند التشخيص او في المخرجات السريرية. وقد أجريت هذه الدراسة في مركز النظائر المشعة بالخرطوم في قسم بنك الدم في الفترة من  2أغسطس الي 20سبتمبر 2008. الهدف : الهدف من هذه الدراسة هو الكشف عن الاضداد منيعة الذات بين مرضى ابيضاض الدم الليمفاوي المزمن. الطريقة:  تم جمع 2مل من الدم الوريدي لعدد 50 مريض من الجنسين و من مختلف الأعمار. تم الكشف عن الاضداد منيعة الذات في كل العينات باستخدام اختبار كومبس المباشر وبتقنية الانتشار المناعي في الجل. وتم استخدام استبيان (مختبر مسبقا ) لجمع البيانات النوعية. النتائج : أظهرت نتائج التحليل أن 38٪ من مرضى ابيضاض الدم الليمفاوي المزمن لديهم اضداد منيعة الذات. وأكدت النتائج أيضا وجود فرق معنوي عند مقارنة ظهور الاضداد منيعة الذات و نوع الوظيفة (0.004)، ومدة المرض (0.019) وليس هناك فرق معنوي  بين ظهور الاضداد  والعمر (0.051)، وكذلك جنس المرض(0.960). التوصيات : يجب الكشف عن الاجسام المضادة لدي كل مرضي ابيضاض الدم اليمفاوي المزمن ، حيث انه  يمكن أن يساعد في المعالجة و السيطرة على تطور المرض وتحسين مستقبله.